Этико-правовые аспекты регулирования применения технологий искусственного интеллекта - Сулейков, Андрей (ՀՀ ԳԱԱ ՏԻ)
The technology of artificial intelligence (AI) as such is complex in nature. The main difference between AI and classical analytical systems or software products that allow the selection and classification of data is the ability to perform cognitive functions that were previously only available to the higher nervous activity of a rational being - a human. In this article, the issues of ethical and legal regulation of the use of AI technologies are considered, the general analysis of the development process of AI regulation according to the principle "from general to private" is conducted, a brief description of the most significant levels of acts aimed at regulating this technological direction is given. Special emphasis is placed on the specifics of AI as a technical-technological complex, as well as on ethical and fundamentally legal contradictions caused by the nature of AI. The main approaches to the issue of giving AI legal personality are considered, and the role of various types of ethical acts in this area as a regulatory tool are discussed. Արհեստական բանականության տեխնոլոգիան, որպես այդպիսին, իր բնույթով բարդ է. ԱԲ-ն ավելի շատ տարբեր տեխնոլոգիական, կազմակերպչական և ծրագրային լուծումների համադրություն է, քան հստակ ձևակերպված և ստանդարտացված տեխնոլոգիա: ԱԲ-ի և դասական վերլուծական համակարգերի կամ ծրագրային արտադրանքների միջև հիմնական տարբերությունը, որը թույլ է տալիս տվյալների ընտրություն և դասակարգում, ճանաչողական գործառույթներ կատարելու ունակությունն է, որոնք նախկինում հասանելի էին միայն ռացիոնալ էակի՝ մարդու ավելի բարձր նյարդային գործունեությանը: Технология искусственного интеллекта как таковая является комплексной по своей природе: ИИ представляет собой скорее совокупность различных технологических, организационных и программных решений, чем четко формулируемую и стандартизируемую технологию. Главным отличием ИИ от классических аналитических систем или программных продуктов, позволяющих проводить отбор и классификацию данных, является возможность осуществлять когнитивные функции, ранее доступные только высшей нервной деятельности разумного существа – человека.
Keywords: Искусственный интеллект